"Good Riddance to the Stinkin' Place": Deindustrialisation and Memory at Associated Pulp and Paper Mills in Burnie, Tasmania. (1st November 2015) - Barton, Ruth
Abstract : As areas have deindustrialised, the factories that once symbolised prosperity and constancy are abandoned. These buildings are imbued with the memories of the workers and local people and can become the site of contest over visions of the past, present and future. In Burnie, Tasmania, the Associated Pulp and Paper Mills factory closed in 2010 and was demolished in 2012. There was a sense of ambivalence around these buildings that had dominated Burnie physically and economically for over 75 years. Their centrality to the town's prosperity and growth went largely uncelebrated and they were demolished to erase memories of the industrial past and frame the future as post-industrial.